Analysis of the Concept of Patient Identification Noncompliance as a Risk Factor for Care Errors - Pratiwi Ari Hendrawati; Siti Aisah; Aric Vranada (Jurnal Indonesia Sosial Sains, 2026)
Accurate patient identification is a main goal of patient safety in health services, as it prevents mistreatment that can cause serious injury or death. Yet, nursing practice shows ongoing non-compliance by health workers with standard procedures, raising medical error risks. Thus, systematically studying non-compliance with patient identification as a mistreatment risk factor is essential. This study analyzes the concept of patient identification non-compliance via Walker and Avant's eight-stage approach. Data came from a systematic review of 60 peer-reviewed articles (2011–2025) from PubMed, Google Scholar, and ScienceDirect. Results reveal characteristics like failure to follow standards, pre-intervention occurrence, health worker involvement, and intentional/unintentional nature. Antecedents include individual factors, service systems, and work environments. Consequences encompass heightened mistreatment risk, procedural errors, patient injuries, legal/psychological impacts on nurses, and institutional losses. In conclusion, non-compliance with patient identification is a key patient safety concept and triggers major mistreatment. Strengthening compliance requires continuous education, system support, and robust safety culture in facilities.